CHANGE OF DRIVER’S RESPONSE TIME DEPENDING ON LIGHT SOURCE AND BRAKE LIGHT TECHNOLOGY USED - Petr JILEK; Luboš VRÁBEL (Scientific Journal of Silesian University of Technology. Series Transport)
This paper deals with finding out the influence of the type of light source of car brake lights on the reaction time of the driver of the preceding vehicle. The driver’s reaction time was measured in the form of pressing the brake pedal depending on the lighting of brake lights on the leading vehicle. The measurement evaluation consists of a comparison of the phase shift between the brake light signal of the first vehicle and the brake light signal of the second vehicle. The experimental measurement was performed for five people using the classic light bulb, afterwards, an LED light source for the brake lights of the first vehicle. The records confirmed that the driver’s reaction time depends on many factors, with the source and intensity of the brake lights also playing an important role. Further, it affects the reaction time and the activity or inactivity of the rear sidelights. The reaction time of the driver of the preceding vehicle was extended with their activation.